2021
DOI: 10.3390/genes12091333
|View full text |Cite
|
Sign up to set email alerts
|

miR-27b-3p a Negative Regulator of DSB-DNA Repair

Abstract: Understanding the regulation of DNA repair mechanisms is of utmost importance to identify altered cellular processes that lead to diseases such as cancer through genomic instability. In this sense, miRNAs have shown a crucial role. Specifically, miR-27b-3 biogenesis has been shown to be induced in response to DNA damage, suggesting that this microRNA has a role in DNA repair. In this work, we show that the overexpression of miR-27b-3p reduces the ability of cells to repair DNA lesions, mainly double-stranded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…MiRNA is predominantly implicated in the suppression of mRNA expression by targeting the 3' UTR of specific genes. One such miRNA, MiR-27b-3p, has been identified as a potential tumor suppressor across various cancer types 33 . Investigations have demonstrated that MiR-27b-3p exerts a negative regulatory effect on DNA repair and exhibits diminished expression in lung cancer tissues 34 .…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA is predominantly implicated in the suppression of mRNA expression by targeting the 3' UTR of specific genes. One such miRNA, MiR-27b-3p, has been identified as a potential tumor suppressor across various cancer types 33 . Investigations have demonstrated that MiR-27b-3p exerts a negative regulatory effect on DNA repair and exhibits diminished expression in lung cancer tissues 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the presence of a particular miRNA, miR-27b-3p, which is responsible for the regulation of CYP1B1 [ 19 , 37 , 38 , 39 , 40 ] and is involved in renal diseases [ 41 ]. In breast cancerous tissues miR-27b-3p level is decreased compared to non-cancerous tissues, leading to the high expression of CYP1B1 [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…At renal level, the CYP1B1 overexpression induced in RPTEC by tARPC can be interpreted as an attempt to protect RPTEC from cisplatin-induced nephrotoxicity and may open an important strategy of prevention of AKI before starting chemotherapy. In this study, we investigated the presence of a particular miRNA, miR-27b-3p, which is responsible for the regulation of CYP1B1 [19,[37][38][39][40] and is involved in renal diseases [41]. In breast cancerous tissues miR-27b-3p level is decreased compared to non-cancerous tissues, leading to the high expression of CYP1B1 [42,43].…”
Section: Discussionmentioning
confidence: 99%